Implementation of Internal Quality Assurance Management in Meeting Educational Facility and Infrastructure Standards - Zahrotun Ni’mah Afif; Mar’atul Azizah; Lia Miftahur Rohmah; Muhammad Fadhlan Refa (At Tadbir: Islamic Education Management Journal, 2025)
This study aims to analyse the implementation of Internal Quality Assurance Management (MPMI) in meeting National Education Standards (SNP), particularly in terms of facilities and infrastructure at SMP Negeri 5 Jombang. The research approach used is descriptive qualitative with data collection techniques through interviews, observation, and documentation, as well as interactive data analysis through the stages of reduction, presentation, and conclusion drawing. The results of the study indicate that the implementation of IQM at SMP Negeri 5 Jombang has been carried out systematically through the Plan–Do–Check–Act (PDCA) cycle as stipulated in Permendikbud No. 28 of 2016. The quality mapping process was carried out through participatory School Self-Evaluation (EDS), the results of which were integrated into programme planning, teacher competency development, and data-based facility and infrastructure management. The school also implemented open monitoring and evaluation to ensure the sustainability of quality improvement. This research contributes to the development of educational management theory by strengthening the concept of participation-based Total Quality Management (TQM) and evidence-based planning. The findings are expected to serve as a practical reference for other educational units in building an adaptive, transparent, and sustainable quality culture through the implementation of an integrated internal quality assurance system.